Anti-atopic activities of mixture herbal aqua extracts - Lee, Bo Kyung; Moon, So Jeong; Kim, Hyun Sook; Jung, Yi Sook (Journal of the Korean Society of Food Science and Nutrition, 2018)
Atopic dermatitis (AD) is one of the most common inflammatory skin diseases and is affected by genetic, environmental, and immunologic factors. This study evaluated the anti-atopic efficacy of mixture herbal aqua extract (MHAE), including Houttuynia cordata, Portulaca oleracea, Acanthopanacis cortex, Astragalus membranaceus, and Asparagus cochinchinensis. MHAE significantly increased both 2,2-diphenyl-1-picrylhydrazyl and 2,2’-azino-bis(3-eth-ylbenzothiazoline-6-sulfonic acid) scavenging activities in a concentration-dependent manner (EC 50 =6.74 and 21.70 mg/mL), respectively. The anti-atopic effects of MHAE were evaluated by measuring repression of the thymus and activation-regulated chemokine (TARC/CCL17) and macrophage-derived chemokine (MDC/CCL22) production. The anti-inflammatory effects of MHAE were assessed by measuring the mRNA levels of interleukin (IL)-4,-13, and-1β. As a result, MHAE showed repression of CCL17 and CCL22 in tumor necrosis factor-α plus interferon-γ-induced HaCaT cells, and the mRNA levels of IL-4,-13, and-1β were inhibited by MHAE in lipopolysaccharide (LPS)-induced phorbol myristate acetate-stimulated THP-1 cells. These results suggest that MHAE exhibited anti-atopic activity via regulation of antioxidant and anti-inflammatory activities. Taken together, these results demonstrate that various mixed herbs possess potent anti-atopic activities and might be utilized as promising agents in the field of health products. Further studies for the identification of active compounds from medicinal herbs are clearly needed.
Keywords: Anti-atopic; Anti-inflammation and antioxidant; Atopic dermatitis; Mixture herbal aqua extract